Transvaginal ultrasonography compared with Bishop score for predicting cesarean section after induction of labor - Bastani P; Hamdi K; Abasalizadeh F; Pourmousa P; Ghatrehsamani F (Dove Medical Press, 2011)
Parvin Bastani, Kobra Hamdi, Fatemeh Abasalizadeh, Parisa Pourmousa, Fatemeh GhatrehsamaniWomen's Reproductive Health Research Center, Tabriz University of Medical Sciences, Tabriz, IranBackground: Reproductive health researchers are interested in finding better methods for predicting an unwanted type of delivery after induction of labor. The aim of this study was to compare the value of transvaginal ultrasonography findings and the Bishop score in predicting cesarean section after induction of labor.Methods: Two hundred women with singleton pregnancies undergoing induction of labor at 37–42 weeks were enrolled in this prospective study. Transvaginal investigation was done for all participants prior to induction. To compare the predictive value of the methods, receiver-operating characteristic (ROC) curves were plotted and equality of the area under curve (AUC) was tested.Results: The mean age of the participants was 29.9 years, mean gestational age was 39.6 weeks, and mean gravid was 1.5. The AUC calculated for Bishop score was 0.39 (95% confidence interval [CI] 0.3–0.48). The AUC for cervical length measured by ultrasonography was 0.69 (95% CI 0.6–0.77). The AUC for the posterior cervical angle measured by ultrasonography was 0.38 (95% CI 0.29–0.47). Testing equality of the ROC curves for these three methods showed the ROC for cervical length to be statistically different from both Bishop score and posterior cervical angle (P < 0.001). However, the difference in ROC area compared between Bishop score and posterior cervical angle was not statistically significant.Conclusion: Based on our findings and available information in the literature, it seems that cervical length measured by transvaginal ultrasonography has the potential to replace the traditional Bishop score, provided that such a facility is available when needed.Keywords: induction of labor, Bishop score, transvaginal ultrasonography, cesarean section, diagnostic value